“GREENING” THE JOURNEY OFEXPLORATION: EXAMINING SUSTAINABLE TOURISM IN CENTRAL VIETNAM THROUGH THE PERCEPTIONS AND BEHAVIORAL RESPONSES OF MODERN-DAY TOURISTS - THUY, THAN TRONG; TRUONG, TRAN NHAT; THU, NGUYEN THI MONG (Journal of Posthumanism, 2025)
In this study, the author integrated the Theory of Planned Behavior (TPB) and the Value-Belief-Norm (VBN) theory of green consumer behavior to collect and analyze data. The research findings indicate that all hypotheses were supported with high statistical significance (P < 0.001), reflecting the model's strong fit with the actual data. Three factors were found to influence Attitude toward Green Tourism: Personal Contribution to Environmental Protection (β = 0.411), Environmental Mindfulness (β = 0.311), and Environmental Knowledge (β = 0.309). Among these, personal contribution exerted the strongest effect, suggesting that daily pro-environmental actions play a crucial role in shaping a positive attitude toward sustainable tourism. Moreover, AGT had a very strong impact on the Intention to Participate in Green Tourism (β = 0.729), emphasizing attitude as a fundamental driver of behavioral intention. This intention further significantly influenced Sustainable Tourism Behavior (β = 0.711), confirming the mediating role of intention in transforming attitude into actual behavior. These findings reinforce the theoretical assumptions of both TPB and VBN, highlighting the importance of awareness and individual actions in promoting green tourism.